Android Based Switch Controlling Technique for LED Bulbs Using Bluetooth/Wi-Fi Technology - Munigoti Saikiran; Lalith Nagaram Nagarajan; Malladi Bharath (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
This paper presents an efficient approach to switch on/off and control the intensity of an LED bulb from a remote place using Android Applications installed in a Smartphone. As LED household bulbs and lights are energy efficient, drop-in replacements for the incandescent lighting found in homes and offices. These lights produce a warm brightness while providing a significant cost savings over traditional lighting. Bluetooth & Wi-Fi modules are used simultaneously as an interface that make connection between Android Application and the LPC2148 controller by which the generated output can be viewed with the help of an LED bulb and control various other devices, based on the availability in particular areas.